Race and gender in the classroom : teachers, privilege, and enduring social inequalities - Stoll, Laurie Cooper (Lexingon Books, 2013)
Race and Gender in the Classroom explores social inequalities in education in the current era of "post-racial" and "post-gendered" politics. In particular, this book illuminates the obstacles that mitigate the potential for teachers to serve as social justice advocates in the classroom by connecting teachers' behaviors and attitudes to the institutional complexes in which they participate